Mung Bean Juice Consumption to Pregnant Women with Mild Anemia - Sri Martini; Rosmala Kurnia Dewi (Jurnal Profesi Bidan Indonesia, 2021)
Background: World Health Organization (WHO) (2015) mention that around 800 women died from complications of pregnancy and child birt because of anemi. Anemia is the biggest and most difficult micronutrient problem to overcome in the world (Lynch, 2011). Iron deficiency anemia is the most common nutritional problem in the world and affects more than 600 million people (Arisman, 2010). Mung beans also contain iron, vitamin C and zinc which play a role in treating iron deficiency anemia. Purpose: To determine the effect of giving mung bean juice to pregnant women with mild anemia. Method: This research uses a qualitative descriptivee with a case study (Case Study). The instrument used the varney's seven-step care and progress notes using subjective, objective, data analysis and management (SOAP). Results: The results of evaluation from management that have been carried out for 1 month with monitoring 4 visits, it was found that there was an increase in Hb levels, namely from the initial inspection on 7 June 2020 with Hb of 10 g%, and on the last visit on 7 July 2020 there was an increase in Hb to 11 gr%. Conclusion: Giving green bean juice can support an increase in Hb levels because green beans contain vitamin C which helps in absorbing Fe.